Efektivitas E-Lampid sebagai Inovasi Pelayanan Publik di Bidang Administrasi Kependudukan Kota Surabaya - Nabila Brilianti Putri; Miftachul Salis; Aris Sudaryanto (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2021)
Public services for every citizen is an important role in human life from they are born until die. Effective public service is a hope for the community. Like the case at the Dispendukcapil Surabaya, Surabaya residents expect the service process to be effective. However, the service process at the Dispendukcapil Surabaya gave birth to problems and ended up with complaints and disappointments from Surabaya residents. Therefore, Dispendukcapil Surabaya tried to overcome this problem by giving birth to an innovation, namely E-LAMPID (Electronic, Born, Died, Moved, Came). This article aims to know how the effectiveness of E-LAMPID innovation in the Dispendukcapil Surabaya. This research uses a descriptive-analytic method by utilizing secondary data sources. These resources have been very helpful in supporting the analysis of the authors in this article. The result achieved is the ease of public services at the Surabaya Civil Registration Office because of the E-LAMPID innovation. The conclusion is that by implementing E-LAMPID, services at the Dispendukcapil Surabaya can be more effective than the manual service model.